The thin executioner - Shan, Darren (Little, Brown, 2010)
In a nation of warriors where weakness is shunned and all crimes, no matter how minor, are punishable by beheading, young Jebel Rum, along with a slave who is fated to be sacrificed, sets forth on a quest to petition the Fire God for invincibility, but when the long and arduous journey is over, Jebel has learned much about fairness and the value of life.